Seismic performance of precast composite shear walls reinforced by concrete-filled steel tubes. (1st May 2018) - Wu, Liwei; Tian, Ying; Su, Youpo; Chen, Haibin
Highlights: A new type of precast composite shear wall was proposed and experimentally studied. CFSTs completely replaced reinforcing bars in the boundary elements of RC walls. Sleeve-mortar connections with proposed detailing can reliably transfer loads. The CFST walls presented better strength and deformation capacity than RC walls. Abstract: A type of precast slender composite shear wall was proposed and experimentally studied. In this new precast structural wall system, concrete-filled steel tubes (CFSTs) were used to entirely replace the longitudinal reinforcement in the boundary elements of conventional reinforced concrete (RC) shear walls. At joints, the CFSTs and wall web reinforcement were connected by sleeves filled with high-strength mortar. To examine the seismic performance of the proposed system, seven 1/3-scale specimens were built and tested under quasi-static and dynamic cyclic lateral loading with a top displacement rate up to 20 mm/s. Major test variables included axial force ratio ranging from 0.075 to 0.19 and loading rate. This paper reports the damage pattern, hysteretic load-deformation response, energy dissipation capacity, and connection performance of the test specimens. Under the considered axial force levels and loading rates, lateral loads were successfully resisted at the joints and the response of all specimens was dominated by flexure. The use of CFSTs increased lateral strength and deformation capacity. The highest axial force ratio caused drift capacity to be reduced from 2.5% to 2.0%. Although loading rate nearly had no influence on either lateral stiffness or strength, it reduced energy dissipation capacity. Finally, the effectiveness of proposed detailing of sleeve-mortar connections in load transfer was validated by the similar hysteric response, joint opening, and wall sliding between monolithic and precast CFST wall specimens.